Legal Protection Against Execution Dependent Rights In Conventional Banks - Siti Komariah; Otom Mustomi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
. Legal Protection for the Implementation of Execution of Dependent Rights in Conventional Banks, which includes Research Objectives. For legal protection of the mechanism for the execution of the right of dependency in the return of debtors to the convention bank. Analyze the settlement of cases against bad debtors' assets to traditional banks and the execution of dependant rights in the process of loan repayment. How far studies on dependent rights execution in traditional banks have gone in terms of legal protections. Procedures for Conducting Studies The studies utilized are of a legal normative type. The study's findings Law 49/Prp of 1960, pertaining to the State Receivables Affairs Committee (PUPN Law), protects the right of dependents to the return of debts owed by government commercial banks. It is the responsibility of the State Receivables Affairs Committee (